2006
DOI: 10.4049/jimmunol.177.10.7059
|View full text |Cite
|
Sign up to set email alerts
|

TLR-Dependent Induction of IFN-β Mediates Host Defense against Trypanosoma cruzi

Abstract: Host resistance to the intracellular protozoan parasite Trypanosoma cruzi depends on IFN-γ production by T cells and NK cells. However, the involvement of innate immunity in host resistance to T. cruzi remains unclear. In the present study, we investigated host defense against T. cruzi by focusing on innate immunity. Macrophages and dendritic cells (DCs) from MyD88−/−TRIF−/− mice, in which TLR-dependent activation of innate immunity was abolished, were defective in the clearance of T. cruzi and showed impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
91
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 48 publications
7
91
2
4
Order By: Relevance
“…This result prompted the conclusion that the death or killing of T. cruzi by host cells was required to release agonists of TLR9 (34). Macrophages and DC appear to have a more potent PRR-dependent responses to T. cruzi (35), related perhaps to their higher expression and diversity of PRR and to their enhanced phagocytic and cytotoxic activity relative to other host cells. The ability of T. cruzi to invade many different host cells other than these phagocytic cells, as well as to quickly exit phagolysosomes, might also assist in avoiding early immune system recognition.…”
Section: Discussionmentioning
confidence: 99%
“…This result prompted the conclusion that the death or killing of T. cruzi by host cells was required to release agonists of TLR9 (34). Macrophages and DC appear to have a more potent PRR-dependent responses to T. cruzi (35), related perhaps to their higher expression and diversity of PRR and to their enhanced phagocytic and cytotoxic activity relative to other host cells. The ability of T. cruzi to invade many different host cells other than these phagocytic cells, as well as to quickly exit phagolysosomes, might also assist in avoiding early immune system recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Despite observations that T. cruzi elicits a prominent type I IFN response early in infection (10,13,52), it is presently unclear if type I IFNs play a role in innate resistance to T. cruzi (12,22,51). The goal of the present study was to determine whether type I IFN-dependent signaling plays a role in innate host resistance to T. cruzi infection.…”
mentioning
confidence: 97%
“…Cytokines produced during acute infection, such as interleukin-12 (IL-12), tumor necrosis factor alpha (TNF-␣), and gamma interferon (IFN-␥), as well as nitric oxide, play critical roles in controlling T. cruzi infection in the acute stage of infection (33). In addition, T. cruzi triggers a TLR-independent type I IFN response (9) in isolated cells and in murine models of acute infection (10,12,21,22,51,52).…”
mentioning
confidence: 99%
“…These data implicate Irgm3 in restricting Toxoplasma gondii (22,23) and C. trachomatis (16) survival; Irgm1 in restricting Mycobacterium tuberculosis (24), Trypanosoma cruzi (25), and Toxoplasma gondii (22); Irga6 in restricting T. gondii (21); and Irgd in restricting T. cruzi (26). Because IRG proteins often localize to pathogen-containing vacuoles as the pathogen enters the host cell and remain with the vacuole as it is processed (20,22), it has been suggested that the proteins regulate processing of pathogen-containing vacuoles, thereby governing growth and survival of the pathogen.…”
mentioning
confidence: 98%